Castanea mollissima shell polyphenols regulate JAK2 and PPARγ expression to suppress inflammation and lipid accumulation by inhibiting M1 macrophages polarization - Suwen Liu; Zhang Lu; Chang Liu; Xuedong Chang; Buhailiqiemu Apudureheman; Shiguo Chen; Xingqian Ye (Journal of Functional Foods, 2022)
Castanea mollissima shells are a by-product of Chinese chestnut processing and contain many polyphenols. Macrophage polarization plays an important role in the progression of atherosclerosis (AS). We investigated the action of Castanea mollissima shell polyphenols (CSPs), with proanthocyanidin C1 and proanthocyanidin B1 as the main phenolic components, on macrophages. CSPs (40 μg/mL) significantly decreased inflammatory cytokines secretion in M1-type macrophages (p < 0.01). The addition of AG490, a JAK2 inhibitor, enhanced the regulatory effect of CSPs. CSPs also significantly upregulated the protein expressions of PPARγ, LXRα, and ABCA1/G1 (p < 0.01); however, this effect was inhibited by adding the PPARγ blocker GW9662. Therefore, CSPs possibly inhibit M1 type macrophage polarization to reduce inflammation by inhibiting the JAK2/STAT3 signaling pathway; however, it is not dependent on this. Furthermore, the activation of the PPARγ-LXRα-ABCA1/G1 pathway increases cholesterol efflux. Our study suggests that CSPs may act as functional food agents in the prevention of and adjuvant therapy for atherosclerosis.